The two faces of microorganisms in traditional brewing and the implications for no- and low-alcohol beers - Roselli, Giulia E.; Kerruish, Daniel W. M.; Crow, Matthew; Smart, Katherine A.; Powell, Chris D. (Frontiers in Microbiology, 2024)
The production of alcoholic beverages is intrinsically linked to microbial activity. This is because microbes such as yeast are associated with the production of ethanol and key sensorial compounds that produce desirable qualities in fermented products. However, the brewing industry and other related sectors face a step-change in practice, primarily due to the growth in sales of no- and low-alcohol (NoLo) alternatives to traditional alcoholic products. Here we review the involvement of microbes across the brewing process, including both their positive contributions and their negative (spoilage) effects. We also discuss the opportunities for exploiting microbes for NoLo beer production, as well as the spoilage risks associated with these products. For the latter, we highlight differences in composition and process conditions between traditional and NoLo beers and discuss how these may impact the microbial ecosystem of each product stream in relation to microbiological stability and final beer quality.